A two-dimensional material thin layer peeling and synchronous dispersion device and method thereof

CN118239480BActive Publication Date: 2026-10-27XI AN JIAOTONG UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410344704.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-25
Publication Date
2026-10-27
Estimated Expiration
2044-03-25

AI Technical Summary

Technical Problem

[0014]二维材料的剥离主要包含化学剥离和机械剥离两种方法,受限于化学剥离的反应过程,使用化学剥离时的氧化还原过程往往使材料产生缺陷,并不能广泛应用于电子器件方面

Benefits of technology

[0034]一种二维材料薄层剥离并同步分散方法,全程为物理过程,不存在化学反应,能够同时实现二维材料薄层的制备和分散,通过一步能够完成其他技术多步才能实现的效果;待处理物料与二维材料不直接接触,避免了污染;与所用二维材料为球体(如石墨球)价格低廉,可重复利用,所用设备结构简单;对于待处理物料粉体的限制少,能够处理各种尺寸、形貌的粉体,并且还能处理浆料、液体等;制备过程无游离的二维材料碎片掉落,产率100%,产品品质好;对于同类二维材料,可连续制备,无需清洗即可重复使用,生产效率高;适合规模化生产应用,可工业化。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118239480B_ABST
    Figure CN118239480B_ABST
Patent Text Reader

Abstract

The application discloses a two-dimensional material thin layer stripping and synchronous dispersion device and method, two-dimensional material thin layer raw materials are put into a material source bin, the weight of the two-dimensional material thin layer raw materials and the material source bin is weighed to obtain initial mass A; mass B of to-be-uniformly-doped materials is put into a material bin; an eccentric motor is used to drive the two-dimensional material thin layer raw materials to roll and collide, the two-dimensional material thin layer is induced to be stripped from the surface of the two-dimensional raw material ball and separated through a material screening sieve, and meanwhile, the to-be-uniformly-doped materials are self-mixed in a spiral track; the material source bin and the two-dimensional material thin layer raw materials in the material source bin are weighed to obtain mass A n ; the two-dimensional material thin layer mass C added into the mixture is obtained by subtracting mass A n from the initial mass A; and the material with the two-dimensional material thin layer mass fraction of 1 / 2 is obtained. The whole process is simple in process, low in cost, high in efficiency, high in product purity and suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of new energy materials technology, specifically relating to a device and method for the simultaneous exfoliation and dispersion of two-dimensional material thin layers. Background Technology

[0002] In recent years, with the rapid development of new energy sources and electronic devices, energy conversion and energy storage have become crucial issues that urgently need to be addressed. Currently, common energy storage methods include batteries and capacitors. Batteries have been extensively studied due to their advantages such as high specific capacity and suitability for large-scale commercial production. Among them, environmentally friendly lithium-ion batteries (LIBs) have attracted considerable attention due to their high operating voltage and energy density, especially the low toxicity and environmental friendliness of their electrode materials.

[0003] As an indispensable component of lithium-ion batteries, the cathode material directly determines important performance characteristics such as battery capacity, lifespan, and safety. Currently, common cathode materials for lithium-ion batteries include layered lithium transition metal oxides (LiMO2, M = Co, Ni, Mn, etc.), manganese spinel (LiMn2O4), and polyanionic compounds (Li...). x M y (XO4)Z (M = Fe, Mn, Co, V, etc., X = P, Si, S, etc.). With the recent surge in electric vehicle development, the development of batteries with faster charge / discharge rates, higher charge / discharge ratios, and greater safety has become a hot research topic. However, the development of these two materials is limited by the structural instability of layered lithium transition metal oxide materials and the safety issues arising from side reactions between manganese-based spinel materials and the electrolyte.

[0004] Lithium iron phosphate (LiFePO4, LFP), as a polyanionic cathode material, possesses a stable discharge plateau (~3.4V) and a high discharge specific capacity (~170mAh / g). This material exhibits good cycle stability, thermal stability, and is made from inexpensive and readily available raw materials. In particular, it is safe and environmentally friendly, making it considered one of the most suitable cathode materials for lithium-ion batteries, attracting widespread attention. Currently, most research focuses on improving the low ionic and electronic conductivity caused by the olivine lattice structure of lithium iron phosphate. Researchers commonly employ carbon layer coating of lithium iron phosphate particles to improve their rate performance. Chen et al. successfully constructed a novel ultrathin layer structure composed of LiFePO4 / C nanoparticles through squaric acid-induced evaporation self-assembly. LFP retains the unique morphology of squaric acid cyanine as a template, which can effectively reduce the diffusion distance of lithium ions and increase the contact between the electrode and the electrolyte. However, when carbon coating is combined with nanoscale LFP, the specific surface area of ​​the material increases significantly. To obtain a uniform and effective carbon coating, a large amount of carbon is introduced, which will greatly reduce the energy density of the battery. Conversely, a small amount of carbon doping will lead to an uneven carbon coating, which is not conducive to improving the conductivity of LFP.

[0005] Graphene (GN), a two-dimensional material, has been a popular subject of scientific research since its discovery. Due to its excellent mechanical strength, high thermal conductivity, and electron mobility, it has been extensively studied in biomedical materials, sensor materials, and electrode materials, and is considered one of the important materials for battery modification. Compared with traditional carbon black additives, graphene not only has better conductivity, but its softness also allows for better coating of lithium iron phosphate powder, providing more effective contact. The more complete conductive network formed by larger areas of continuous graphene significantly improves the conductivity of the cathode material. Currently, researchers typically use the following three methods to prepare GN / LFP composite materials.

[0006] (1) Synthesis of lithium iron phosphate on graphene

[0007] The unique two-dimensional structure of graphene effectively restricts the growth of lithium iron phosphate (LFP) particles on it, reducing the microscopic particle size to the nanoscale. This synthesis method has advantages in both carbon coating and nano-sizing, and the composite of LFP on graphene also reduces the agglomeration problem of graphene. Yuan et al. synthesized rGO / LiFePO4 via a simple solid-state combined carbothermal reduction method. The prepared rGO / LiFePO4 exhibited good crystallinity, with active material particles connected by uniform graphene, resulting in significantly improved cycle stability.

[0008] Li et al. prepared a GN / LFP hybrid conductive network via a hydrothermal method and then used the Hummers method to prepare graphene oxide from natural graphite powder mixed with lithium iron phosphate precursors (ferrous sulfate, H3PO4, LiOH). Lithium iron phosphate was synthesized on the surface of the graphene oxide as a template, yielding good crystallinity. When the graphene doping concentration was 8 wt%, the samples exhibited capacities of 160.3 mAh / g and 81.5 mAh / g at 0.1C and 10C rates, respectively.

[0009] (2) Self-assembly of graphene

[0010] In-situ self-assembly of GN was induced on the exterior of lithium iron phosphate particles. The self-assembled GN not only better prevents the dissolution of the lithium iron phosphate electrode in the electrolyte during cycling, but also allows for more reliable control of the GN coating thickness by adjusting the processing technology. Ma et al. used ferrocene as a catalyst to synthesize a highly graphitized carbon layer in situ on lithium iron phosphate nanosheets. The (010) crystal plane of lithium iron phosphate, i.e., the direction of electron transfer in lithium iron phosphate, is exposed, which is beneficial to improving its electronic conductivity. Thanks to the rapid electron transport through the graphene layer and the efficient diffusion of lithium ions on the thin nanosheets, the graphene / lithium iron phosphate material exhibits good electrochemical performance at both high rates (100°C) and low temperatures (-20°C).

[0011] (3) Mechanical mixing

[0012] The simplest method for preparing GN / LFP is mechanical mixing. The most common mechanical mixing methods include ultrasonic treatment and mechanical ball milling. Rajoba et al. prepared GN / LFP materials using mechanical mixing. They ultrasonically mixed lithium iron phosphate (FeN3O9·9H2O, ammonium dihydrogen phosphate, and LiNO3 as precursors, and C2H5NO2 as fuel) synthesized by solution combustion with graphene oxide (GO). GO uniformly coated the surface of the lithium iron phosphate particles with a thickness of approximately 5 nm, improving the cycle stability of lithium iron phosphate. Adepoju et al. dry-mixed lithium iron phosphate and GN powders and used slurry technology to prepare a hybrid electrode material. Nanoscale LFP particles are interconnected through flat, ultrathin bridges formed by GN sheets to improve the conductivity of lithium iron phosphate.

[0013] Disrupting the van der Waals forces between graphite sheets through mechanical means such as pyrolysis, ultrasonication, and rolling is considered an effective method for preparing graphene. Although there are still shortcomings, mechanical methods are still regarded as an important means for the large-scale production of few-layer graphene.

[0014] The exfoliation of two-dimensional materials mainly includes two methods: chemical exfoliation and mechanical exfoliation. Chemical exfoliation, limited by its reaction process, often introduces defects due to the redox process, limiting its widespread application in electronic devices. Mechanical exfoliation is a low-cost method for preparing high-quality two-dimensional materials. Plasma etching and mild friction methods, suitable for industrial applications, produce high-quality products but in very low yields. Fluid exfoliation requires specialized reaction vessels and stringent reaction conditions. Traditional ball milling requires high flowability of powders or particles; otherwise, exfoliation becomes difficult or the size of the exfoliated material is hard to control, and it easily contaminates the two-dimensional material or powder raw material.

[0015] Traditional ball milling methods use heterogeneous powders, distinct from graphite balls, to grind graphite balls and exfoliate thin layers of graphene. However, this method has significant limitations:

[0016] (1) Graphite spheres will come into direct contact with the powder to be treated, which can easily lead to contamination of the graphite spheres or the powder to be treated. In addition, there is usually a large size difference between the powder and the graphite spheres, which will adhere to the graphite spheres, which is not conducive to the accuracy of subsequent weighing results, and thus it is difficult to accurately control the amount of graphene added during the production process.

[0017] (2) Considering that the powder needs to peel off graphene during the rolling and collision process with the graphite spheres and carry the peeled graphene to disperse, the powder has high requirements for flowability, such as the powder particle size should not be less than 10μm, the powder morphology should be spherical, and the powder needs to be kept dry. Summary of the Invention

[0018] The technical problem to be solved by the present invention is to provide a two-dimensional material thin-layer peeling and simultaneous dispersion device and method to address the shortcomings of the prior art, thereby solving the technical problems of poor conductivity and ion diffusion rate of lithium iron phosphate, and simultaneously realizing the dispersion and preparation of carbon materials in lithium iron phosphate, completing a process that would otherwise require multiple steps in industry in one step.

[0019] The present invention adopts the following technical solution:

[0020] A method for peeling and simultaneously dispersing a thin layer of two-dimensional material includes the following steps:

[0021] Two-dimensional material thin-layer raw material is placed into the material source silo, and the weight of the two-dimensional material thin-layer raw material and the material source silo is weighed to obtain the initial mass A; the material to be uniformly doped with mass B is placed into the material silo.

[0022] An eccentric motor drives a thin layer of two-dimensional material to roll and collide, inducing the two-dimensional material layer to peel off from the surface of the two-dimensional material sphere and separate through a sieve. Simultaneously, the material to be uniformly mixed undergoes self-mixing along a spiral trajectory. The material source silo and its internal two-dimensional material layer are weighed to obtain mass A. n ;

[0023] Subtract mass A from initial mass A n The mass C of the two-dimensional material thin layer added to the mixture was obtained; the mass fraction of the two-dimensional material thin layer was obtained as follows: Materials.

[0024] Preferably, before the two-dimensional material thin-layer raw material is placed into the material source silo, the two-dimensional material thin-layer raw material is first ultrasonically cleaned and dried.

[0025] Preferably, the raw material for the two-dimensional material thin layer is a sphere.

[0026] More preferably, the raw materials for the two-dimensional material thin layer include graphite, BN, WS2, MoS2, SnS2, WSe2, and MoSe2.

[0027] More preferably, the diameter of the two-dimensional material thin film raw material is 1 to 30 mm.

[0028] Preferably, the atmosphere inside the material storage silo includes air, inert gas, and vacuum.

[0029] Preferably, the eccentric motor rotates at a speed of 50 to 6000 rpm.

[0030] Preferably, the material to be uniformly doped includes powder, slurry, and solution. The powder is organic or inorganic powder, and the inorganic powder includes Ti, Al, Mg, Cu, Ni, Fe, TiO2, Al2O3, SiO2, and LiFePO4.

[0031] Another technical solution of the present invention is a two-dimensional material thin-layer peeling and synchronous dispersion device, based on the two-dimensional material thin-layer peeling and synchronous dispersion method, including a material bin, the material bin being disposed below the material source bin, the outer side of the material source bin being connected to the outer side of the material bin through a plurality of fixed springs spaced apart, a material screen being disposed between the material bin and the material source bin, an eccentric motor being disposed below the material screen, and a protective cover on the outer side of the eccentric motor being connected to the material source bin through a plurality of vibration springs spaced apart.

[0032] Preferably, the eccentric motor is a single-phase eccentric motor, a three-phase eccentric motor, or a permanent magnet eccentric motor, and a counterweight is provided on the rotor of the eccentric motor.

[0033] Compared with the prior art, the present invention has at least the following beneficial effects:

[0034] A method for the simultaneous exfoliation and dispersion of two-dimensional materials is disclosed. The entire process is physical, without any chemical reactions, enabling the simultaneous preparation and dispersion of two-dimensional material thin layers. This achieves the effect of multiple steps required by other techniques in a single step. The material being processed does not directly contact the two-dimensional material, avoiding contamination. The two-dimensional material used is spherical (such as graphite spheres), which is inexpensive and reusable. The equipment used has a simple structure. There are few restrictions on the powder content of the material being processed; it can handle powders of various sizes and morphologies, as well as slurries and liquids. No free two-dimensional material fragments fall during the preparation process, resulting in 100% yield and high product quality. For similar two-dimensional materials, continuous preparation is possible, and the material can be reused without cleaning, resulting in high production efficiency. It is suitable for large-scale production applications and can be industrialized.

[0035] Furthermore, since the entire preparation process is conducted in a closed environment, the two-dimensional material thin-layer raw material needs to be ultrasonically cleaned and dried before dispersion preparation to prevent the introduction of moisture or impurities.

[0036] Furthermore, since the two-dimensional material will collide and rub against the screen during the vibration process, in order to ensure a large contact efficiency between the two-dimensional material raw material and the screen to guarantee the preparation rate, the two-dimensional material thin layer raw material needs to be spheres.

[0037] Furthermore, the diameter of the two-dimensional material thin film raw material is 1-30 mm. If the diameter is too large, the displacement of the raw material will be small during vibration, and the friction between the raw material and the screen will also be reduced. If the diameter is too small, the raw material will not be able to vibrate fully in the material source hopper during vibration, which will affect the preparation effect.

[0038] Furthermore, the atmosphere during the preparation process can be air, inert gas, or vacuum. Since the entire preparation process is a closed environment, the atmosphere can be changed according to the type of material, making it suitable for the preparation of different two-dimensional thin-layer materials.

[0039] Furthermore, the eccentric motor operates at speeds of 50–6000 rpm. Too low a speed will prevent the material from gaining sufficient kinetic energy in the feed hopper to rub against the screen, while too high a speed will cause significant centrifugal force and vibration in the entire preparation device, thus shortening its lifespan.

[0040] Furthermore, the material to be uniformly doped includes powder, slurry, and solution. The powder can be organic or inorganic. Inorganic powders include Ti, Al, Mg, Cu, Ni, Fe, TiO2, Al2O3, SiO2, and LiFePO4. The material to be uniformly doped will only vibrate and mix during the preparation process. Therefore, the material to be doped can be powder, slurry, or solution.

[0041] A two-dimensional material thin-layer peeling and synchronous dispersion device is disclosed. The device mainly consists of a raw material bin, a material screen, a material bin, and an eccentric motor from top to bottom. The entire device has a multi-layer structure, which ensures that the two-dimensional thin-layer material raw material can vibrate under the drive of the eccentric motor and collide and rub against the material screen in the closed raw material bin. The peeled two-dimensional thin-layer material can be evenly dispersed in the material bin under the action of gravity and eccentric force. The material to be mixed in the material bin can also be mixed and dispersed with the two-dimensional thin-layer material under the drive of the eccentric motor.

[0042] Furthermore, the counterweight on the eccentric motor is mainly used to increase the centrifugal force, so that the materials in the material bin and the source bin are sufficiently vibrated and dispersed.

[0043] In summary, this invention features simple process, low cost, high preparation efficiency, and good preparation quality.

[0044] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description

[0045] Figure 1 This is a structural diagram of the two-dimensional material thin-layer peeling and synchronous dispersion device of the present invention;

[0046] Figure 2 This is a cross-sectional view of the two-dimensional material thin-layer peeling and synchronous dispersion device of the present invention;

[0047] Figure 3 This is a schematic diagram illustrating the principle of the two-dimensional material thin-layer peeling and simultaneous dispersion method of the present invention.

[0048] Figure 4 This is a schematic diagram showing the state of lithium iron phosphate in the material silo before the two-dimensional material is stripped off according to the present invention.

[0049] Figure 5 This is a schematic diagram showing the state of lithium iron phosphate in the material silo after the graphene nanosheets are dispersed according to the present invention.

[0050] Figure 6 The images show the SEM morphology and EDS elemental analysis of lithium iron phosphate before graphene coating in this invention. (a) shows the microstructure of lithium iron phosphate before coating, (b) shows the surface distribution of Li element in lithium iron phosphate before coating, (c) shows the surface distribution of P element in lithium iron phosphate before coating, (d) shows the surface distribution of Fe element in lithium iron phosphate before coating, (e) shows the surface distribution of O element in lithium iron phosphate before coating, and (f) shows the surface distribution of C element in lithium iron phosphate before coating.

[0051] Figure 7The images show the SEM morphology and EDS elemental analysis of the graphene-coated lithium iron phosphate of the present invention. (a) shows the microstructure of the graphene-coated lithium iron phosphate, (b) shows the surface distribution of Li element in the graphene-coated lithium iron phosphate, (c) shows the surface distribution of P element in the graphene-coated lithium iron phosphate, (d) shows the surface distribution of Fe element in the graphene-coated lithium iron phosphate, (e) shows the surface distribution of O element in the graphene-coated lithium iron phosphate, and (f) shows the surface distribution of C element in the graphene-coated lithium iron phosphate.

[0052] The components include: 1. Sealing cover; 2. Material source silo; 3. Fixing spring; 4. Material silo; 5. Eccentric motor; 6. Vibration spring; 7. Protective cover; 8. Anti-slip mat; 9. Material sieve; and 10. Counterweight. Detailed Implementation

[0053] The technical solution of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0054] Unless otherwise specified, all embodiments and preferred embodiments mentioned herein can be combined to form new technical solutions.

[0055] Unless otherwise specified, all the technical features and preferred features mentioned herein can be combined to form new technical solutions.

[0056] In this invention, unless otherwise specified, percentage (%) or parts refer to weight percentage or parts relative to the composition.

[0057] Unless otherwise specified, the components or preferred components involved in this invention can be combined with each other to form new technical solutions.

[0058] In this invention, unless otherwise specified, the numerical range "a~b" represents an abbreviation of any combination of real numbers between a and b, where a and b are both real numbers. For example, the numerical range "6~22" means that all real numbers between "6~22" have been listed in this document, and "6~22" is simply an abbreviation of these numerical combinations.

[0059] The "scope" disclosed in this invention can be in the form of a lower limit and an upper limit, and can be one or more lower limits and one or more upper limits, respectively.

[0060] In this invention, the term "and / or" as used herein refers to any combination of one or more of the associated listed items, as well as all possible combinations, and includes such combinations.

[0061] In this invention, unless otherwise stated, the various reactions or operation steps may be performed sequentially or in a particular order. Preferably, the reaction methods described herein are performed sequentially.

[0062] Unless otherwise stated, the technical and scientific terms used herein have the same meanings as those familiar to those skilled in the art. Furthermore, any methods or materials similar to or equivalent to those described herein may also be used in this invention.

[0063] Please see Figure 1 and Figure 2 This invention provides a two-dimensional material thin-layer peeling and synchronous dispersion device, including a material source bin 2, a material bin 4, and an eccentric motor 5. The material source bin 2 is disposed on the material bin 4, and a sealing cover 1 is provided on the top of the material source bin 2. The outer side of the material source bin 2 is connected to the outer side of the material bin 4 through a plurality of fixed springs 3 arranged at intervals. The bottom of the material source bin 2 is connected to the material bin 4 through a material screen 9. The material screen 9 is connected to the eccentric motor 5. The bottom of the eccentric motor 5 is fixed to the base through a counterweight 10. An anti-slip pad 8 is provided on the bottom of the base. A protective cover 7 is provided on the outer side of the eccentric motor 5 and the counterweight 10. The protective cover 7 is connected to the material source bin 2 through a plurality of vibration springs 6 arranged at intervals.

[0064] The material source silo 2 is spatially isolated from the lower material silo 4 by the material sieve 9, and the material to be uniformly mixed is stored in the material silo.

[0065] Based on production needs, the eccentric motor 5 can be a single-phase eccentric motor, a three-phase eccentric motor, or a permanent magnet eccentric motor.

[0066] The vibration frequency is adjusted by adjusting the weight of the counterweight 10 on the rotor of the eccentric motor 5, and the vibration amplitude is adjusted by replacing the vibration spring 6 with one of different stiffness.

[0067] The present invention adopts a cage-type layered structure for packaging materials. The eccentric motor 5 drives the rotor with an eccentric shaft to rotate, thereby generating vibration, and the vibration spring 6 constrains the amplitude of the material bin 4.

[0068] First, according to the two-dimensional material raw material on top and powder or slurry on the bottom, they are placed in the material source bin 2 and material bin 4 of the device's layered structure, and the material source bin 2 and material bin 4 are separated by a material screening screen 9;

[0069] Then, the eccentric motor 5 generates vibration, and the appropriate vibration frequency is selected according to the set rotation speed, so that the two-dimensional material thin layer raw material rolls and collides on the material screen 9, realizing the peeling of the two-dimensional material thin layer in the material source bin 2 and passing it through the mesh of the material screen 9 into the powder or slurry of the lower material bin 4.

[0070] Finally, the vibration of the eccentric motor 5 causes the powder or slurry in the lower material bin 4 to tumble and roll, resulting in the uniform dispersion of the peeled two-dimensional material thin layer.

[0071] This invention avoids the complex process of traditionally preparing two-dimensional material thin layers and then dispersing them, greatly reducing uneven dispersion and agglomeration of the two-dimensional material thin layers. Because the two-dimensional material raw material is spatially isolated from the material to be uniformly doped, it does not contaminate the two-dimensional material raw material, and the dispersion process does not impose additional requirements on the particle size and morphology of the material. The entire process is simple, low-cost, highly efficient, produces high-purity products, and is suitable for industrial production. Furthermore, by simply changing the lower layer material and adding an ultrasonic device, the two-dimensional material thin layer peeled off through a sieve can be uniformly dispersed into a solution, providing a simple, non-chemical method for preparing two-dimensional material thin layers suitable for industrial production.

[0072] Please see Figure 3 The present invention discloses a method for peeling and simultaneously dispersing a thin layer of two-dimensional material, comprising the following steps:

[0073] S1. Place the two-dimensional material thin-layer raw material (such as high-purity graphite balls) into a container filled with dilute hydrochloric acid, perform ultrasonic cleaning at room temperature to remove processing residues and easily detachable tiny debris from the surface of the graphite balls, and then dry them.

[0074] Two-dimensional material thin-film raw materials include, but are not limited to, graphite, BN, WS2, MoS2, SnS2, WSe2 and MoSe2.

[0075] Considering the peeling of thin layers of two-dimensional materials through rolling and collision, the preferred material for two-dimensional materials is a sphere with a diameter between 1 mm and 30 mm.

[0076] S2. Place the two-dimensional material sphere into the material source silo and weigh both to obtain the initial mass A;

[0077] The internal atmosphere of the material silo includes, but is not limited to, air atmosphere, inert gas atmosphere and vacuum; the speed of the eccentric motor is 50 rpm to 6000 rpm.

[0078] S3. Weigh the material to be uniformly mixed to obtain an initial mass B, and then put the material with the initial mass B into the material silo.

[0079] The material to be processed can be powder, slurry, or solution; wherein the powder is organic powder or inorganic powder, and the inorganic powder includes, but is not limited to, Ti, Al, Mg, Cu, Ni, Fe, TiO2, Al2O3, SiO2, and LiFePO4.

[0080] There is no limitation on the average size of the powder, including spherical powder, dendritic powder, and irregularly shaped powder.

[0081] S4. Place the sealing cap and the material source hopper on the material hopper from top to bottom, and then hook the fixing spring to the edge of the sealing cap to fix the hoppers together.

[0082] S5. Turn on the power switch. The eccentric motor drives the two-dimensional raw material ball to roll and collide on the material screen, inducing the two-dimensional material thin layer to peel off from the surface of the two-dimensional raw material ball and enter the lower material through the material screen. At the same time, the material in the material bin is self-mixed in a spiral trajectory under the action of the eccentric motor.

[0083] S6. Weigh the raw materials in the material silo and its internal two-dimensional materials at regular intervals to obtain mass A. n Poor quality AA n That is, the mass C of the two-dimensional material thin layer added to the mixture;

[0084] S7. Turn off the power, remove the material from the material hopper, and obtain a uniformly dispersed two-dimensional material thin layer doped with a mass fraction of [missing information].

[0085] The preparation and simultaneous addition of two-dimensional material thin layers is a completely solid-state physical process without any chemical reaction. The product is separated from the two-dimensional material spheres by a spatial isolation method to avoid mutual contact and contamination.

[0086] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. The components of the embodiments of the present invention described and shown in the accompanying drawings can generally be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments of the invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.

[0087] Example

[0088] Using graphite spheres as the source of two-dimensional material, during the exfoliation process, the surface of the graphite spheres collides and rubs against the material sieve, and the resulting graphene thin layer material enters the lower layer of material. Driven by an eccentric motor, the two-dimensional material is uniformly dispersed in the lithium iron phosphate powder, forming a core-shell structure of lithium iron phosphate coated with graphene. The mass ratio of graphene to lithium iron phosphate can be controlled by the exfoliation time, and the relative mass ratio can be between one-thousandth and one-hundredth.

[0089] A method for preparing a core-shell structure of graphene-coated lithium iron phosphate particles includes the following steps:

[0090] a) First, place 10mm diameter high-purity graphite balls into a container filled with dilute hydrochloric acid and perform ultrasonic cleaning at room temperature to remove processing residues and easily detachable tiny debris from the surface of the graphite balls, and then dry them.

[0091] b) Place the graphite balls into the material source silo and weigh them. The total mass of the graphite balls is 955.25g, and the mass of the graphite balls passing through the sieve is 331.06g.

[0092] c) Weigh the lithium iron phosphate powder to be processed to obtain 125.48g of lithium iron phosphate powder, and then put the weighed lithium iron phosphate powder into the material silo.

[0093] d) Stack the sealing cap and material source bin on the material bin from top to bottom, and then fasten the fixing spring to the edge of the sealing cap to fix the bins together. Use a 1000-mesh screen for material screening.

[0094] e) Turn on the power switch. The eccentric motor drives the two-dimensional raw material balls to roll and collide on the material screen, inducing the graphite balls to peel off the surface and produce a graphene thin layer that passes through the material screen into the lower material. At the same time, the lithium iron phosphate in the material bin is self-mixed in a spiral trajectory under the action of the eccentric motor. The graphene from the material bin and the lithium iron phosphate are fully and evenly mixed.

[0095] f) After 90 hours of peeling, the graphite balls and the material passing through the sieve were weighed separately. The graphite balls weighed 954.48 g and the material passing through the sieve weighed 331.16 g, thus obtaining graphene-coated lithium iron phosphate powder with a graphene mass fraction of 0.53%.

[0096] Please see Figure 4 and Figure 5 ,like Figure 4 The lithium iron phosphate powder in the material silo is undoped with graphene. The lithium iron phosphate powder is spread evenly at the bottom of the material silo, such as... Figure 5 This refers to the mixed powder state within the material silo after the graphene is dispersed by vibration. Figure 5 It can be seen that under the drive of the eccentric motor, the lithium iron phosphate in the material bin vibrates and disperses under the action of centrifugal force, and the graphene is also uniformly mixed into the lithium iron phosphate powder during the vibration process.

[0097] Please see Figure 6 ,like Figure 6 Here are the SEM and EDS images of lithium iron phosphate powder, such as... Figure 6 (a) shows lithium iron phosphate particles with a size of approximately 1000 nm. Figure 6 (b)-(f) indicate that the powder has not yet been doped with graphite and only contains Li, P, Fe and O elements.

[0098] Please see Figure 7 ,like Figure 7 The images show the SEM and EDS images of graphene-doped lithium iron phosphate powder, such as... Figure 7 (a) Graphene particles doped into lithium iron phosphate powder, with a size of approximately 1500 nm. Figure 6 (b)-(f) indicates that Figure 6 (a) That is, the doped graphite is surrounded by lithium iron phosphate particles, and the simultaneous preparation and dispersion of graphite in lithium iron phosphate powder is successfully achieved.

[0099] In summary, the present invention provides a device and method for the simultaneous peeling and dispersion of two-dimensional material thin layers. Utilizing an eccentric motor for power, it can simultaneously disperse and prepare two-dimensional thin-layer materials with excellent dispersion and preparation effects. The two-dimensional thin-layer materials are uniformly mixed with the materials to be doped, and the size of the prepared two-dimensional thin-layer materials can be adjusted by the mesh size of the sieve. The preparation speed and dispersion effect can be adjusted by the power of the eccentric motor. This invention achieves a low-cost, high-efficiency method for the peeling and simultaneous dispersion of two-dimensional thin-layer materials, saving process steps, reducing costs, and enabling large-scale industrialization.

[0100] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for the simultaneous peeling and dispersion of a thin layer of two-dimensional material, characterized in that, A two-dimensional material thin-layer peeling and synchronous dispersion device is employed. The device, mainly composed of a material source silo, a screening screen, a material silo, and an eccentric motor from top to bottom, forms a multi-layered structure. This ensures that the two-dimensional thin-layer material vibrates under the drive of the eccentric motor and collides and rubs against the screening screen within the enclosed material source silo. The peeled two-dimensional thin-layer material is evenly dispersed in the material silo under the action of gravity and eccentric force. The material to be mixed and dispersed in the material silo is then mixed and dispersed with the two-dimensional thin-layer material under the drive of the eccentric motor, including the following steps: Two-dimensional material thin-layer raw material is placed into the material source silo, and the weight of the two-dimensional material thin-layer raw material and the material source silo is weighed to obtain the initial mass A; the material to be uniformly doped with mass B is placed into the material silo, wherein the two-dimensional material thin-layer raw material is graphite spheres; An eccentric motor drives a thin layer of two-dimensional material to roll and collide, inducing the thin layer of two-dimensional material to peel off from the surface of the raw material sphere and separate through a sieve. Simultaneously, the material to be uniformly mixed undergoes self-mixing in a spiral trajectory. The raw material silo and its internal two-dimensional material thin layer are weighed to obtain mass A. n ; Subtract mass A from initial mass A n The mass C of the two-dimensional material thin layer added to the mixture was obtained; the mass fraction of the two-dimensional material thin layer was obtained as follows: Materials.

2. The method for peeling and simultaneously dispersing two-dimensional material thin layers according to claim 1, characterized in that, Before the two-dimensional material thin-layer raw material is placed into the material source silo, it is first ultrasonically cleaned and dried.

3. The method for peeling and simultaneously dispersing two-dimensional material thin layers according to claim 1, characterized in that, The diameter of the two-dimensional material thin film raw material is 1~30mm.

4. The method for peeling and simultaneously dispersing a two-dimensional material thin layer according to claim 1, characterized in that, The atmosphere inside the material storage silo includes one or more of the following: air, inert gas, and vacuum.

5. The method for peeling and simultaneously dispersing a two-dimensional material thin layer according to claim 1, characterized in that, The eccentric motor has a speed of 50~6000rpm.

6. The method for peeling and simultaneously dispersing a two-dimensional material thin layer according to claim 1, characterized in that, The material to be uniformly doped includes one or more of powder, slurry, and solution. The powder can be organic or inorganic. The inorganic powder includes one or more of Ti, Al, Mg, Cu, Ni, Fe, TiO2, Al2O3, SiO2, and LiFePO4.

Citation Information

Patent Citations

  • Two-dimensional thin film material coated on microsphere surfaces and simple method for stripping two-dimensional thin film material

    CN107226476A

  • A preparation method of graphene doped alloy anode material for lithium battery

    CN109148866A

  • Flexible vibration separating and screening device

    CN217569576U